Down-Regulation of OsEMF2b Caused Semi-sterility Due to Anther and Pollen Development Defects in Rice - Deng, Luchang; Zhang, Siwei; Wang, Geling; Fan, Shijun; Li, Meng; Chen, Weilan; Tu, Bin; Tan, Jun; Wang, Yuping; Ma, Bingtian; Li, Shigui; Qin, Peng (Frontiers in Plant Science, 2017)
Anther and pollen development are crucial processes of plant male reproduction. Although a number of genes involved in these processes have been identified, the regulatory networks of pollen and anther development are still unclear. EMBRYONIC FLOWER 2b (OsEMF2b) is important for rice development. Its biological function in floral organ, flowering time and meristem determinacy have been well studied, but its role, if only, on male reproduction is still unknown, because null mutants of OsEMF2b barely have anthers. In this study, we identified a weak allele of OsEMF2b, osemf2b-4. The T-DNA insertion was located in the promoter region of OsEMF2b, and OsEMF2b expression was significantly decreased in osemf2b-4. The osemf2b-4 mutant exhibited much more normal anthers than null mutants of OsEMF2b, and also showed defective floret development similar to null mutants. Cytological analysis showed various defects of anther wall and pollen development in osemf2b-4, such as slightly or extremely enlarged tapetum, irregular or normal morphology microspores, and partial or complete sterility. OsEMF2b was highly expressed in tapetum and microspores, and the protein was localized in the nucleus. The expression of 15 genes essential for anther and pollen development was investigated in both WT and osemf2b-4. Fourteen genes including GAMYB was up-regulated, and only PTC1 was down-regulated in osemf2b-4. This suggests that up-regulated GAMYB and down-regulated PTC1 might contribute to the defective anther and pollen development in osemf2b-4. Overall, our work suggests that OsEMF2b plays an essential role during post-meiotic anther and pollen development.